THE EXCLUSION OF ILEGALLY ADMINISTERED EVIDENCE - Eliza Emanuela IONIŢĂ (Challenges of the Knowledge Society)
Both judicial practice and specialized texts have brought up the problem of what the punishment for breaking the legal provisions in the activity of evidence administration is, if a matter of fact had been presented by means that are not legally specified or if a piece of evidence was administered by means that are legally specified, but with the violation of legal provisions. Romania has adhered to the most important international juridical instruments adopted in the sphere of human rights by the adoption, modification or completion of internal legislation. As such, for the first time in Romanian criminal procedural legislation, a sanction for the exclusion of evidence has been introduced, as a corollary for the principle of legality and of loyalty in administering evidence. The New Criminal Procedure Code provides the sanction of exclusion as well, but this time the legislator didn’t resume his or herself to a mere conceptual regulation of the sanction, providing both a specific invalidation procedure as well as procedural solutions. In the New Criminal Procedure Code it is shown that in the sphere of evidence-showing a set of rules has been introduced that establishes the principle of loyalty in the obtainment of evidence. These rules, that provide the sanction of excluding evidence obtained through illegal or unloyal means, will determined the growth of professionalism in the ranks of the judiciary bodies on the subject of obtaining evidence and, on the other hand, will guarantee the firm upholding of the parties rights to a fair trial. “Truth, like all other good things, may be loved unwisely – may be pursued too keenly – may cost too much…” Lord Justice Sir James Lewis Knight-Bruce ”It is a deeply ingrained value in our democratic system that the ends do not justify the means. In particular, evidence or convictions may, at times, be obtained at too high a price”. – Antonio Lamer Former Chief Justice of the Supreme Court of Canada.